2019
DOI: 10.1371/journal.pone.0217179
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of African lions (Panthera leo) in Zambia support movement across anthropogenic and geographical barriers

Abstract: The Luangwa Valley in eastern Zambia is a transverse offshoot of the Great Rift Valley system. This region appears to have an isolating effect as evidenced by suspected endemic subspecies, such as the Cookson’s wildebeest and Thornicroft’s giraffe. Recent mitochondrial DNA studies demonstrated that African lions in Zambia consist of two highly diverse eastern and western sub-populations. Herein, we report nuclear and mitochondrial DNA results from 409 lions that support this population substructure across Zamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 47 publications
(65 reference statements)
1
16
0
Order By: Relevance
“…2014b ; VanHooft et al. 2018 ; Curry et al. 2019 ) levels of gene flow, but this was largely dependent on the amount of connectivity present between sampling locations, for example, isolated populations such as those in the Kainji Lake National Park and Yankari Game Reserve in Nigeria ( Tende et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2014b ; VanHooft et al. 2018 ; Curry et al. 2019 ) levels of gene flow, but this was largely dependent on the amount of connectivity present between sampling locations, for example, isolated populations such as those in the Kainji Lake National Park and Yankari Game Reserve in Nigeria ( Tende et al.…”
Section: Introductionmentioning
confidence: 99%
“…2019 ) levels of gene flow, but this was largely dependent on the amount of connectivity present between sampling locations, for example, isolated populations such as those in the Kainji Lake National Park and Yankari Game Reserve in Nigeria ( Tende et al. 2014b ) and Kafue National Park and the Luangwa Valley Ecosystem in Zambia ( Curry et al. 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The position of major rivers through Africa, in addition to contractions of suitable habitat driven by climate change, are the likely causes of vicariance over 100ka. Suture zones and parapatric (sub)speciation are likely important in maintaining genetic variation ( Bertola et al, 2016 ; Curry et al, 2020 ; Curry, White & Derr, 2019 ; Dures et al, 2020 ). The persistence of major river barriers/corridors in the region, appears to have major biogeographical legacies in terms of defining boundaries between populations and linkage between areas.…”
Section: Discussionmentioning
confidence: 99%
“…Although nuclear diversity has decreased significantly, mtDNA diversity has remained constant over time ( Table 1). Mitochondrial DNA is matrilineally inherited, and localized studies show there is little or no female-mediated gene flow between subpopulations across Africa (32,46,47). Female lions primarily remain with their natal pride while males disperse (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that sampled nuclear genetic diversity reported both high (28)(29)(30) and low (31-33) levels of gene flow, but this was largely dependent on the amount of connectivity present between sampling locations. For example, isolated populations such as those in the Kainji Lake National Park from Yankari Game Reserve in Nigeria (31) and Kafue National Park from the Luangwa Valley Ecosystem in Zambia (32). Genetic differentiation can even be seen between populations within national parks (33).…”
Section: Introductionmentioning
confidence: 99%